1984
DOI: 10.3168/jds.s0022-0302(84)81616-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Premilking Udder Preparation on Bacterial Population, Sediment, and Iodine Residue in Milk

Abstract: Udder preparations that wet both udder surfaces and teats had the highest standard plate count in milk compared with methods that wet teats only. Physical action of cleaning teats with a dry towel lowered bacterial count compared with preparations wetting both udder surfaces and teats. Methods resulting in lowest bacterial counts were the use of water hose, wet towel, or premilking disinfectant teat dip followed by drying with paper towels. Counts of coliform and Staphylococcus sp. followed similar trends. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
6

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 14 publications
4
50
0
6
Order By: Relevance
“…feeds and veterinary fortification with inorganic (KI) or organic (ethylenediamine dihydroiodide, EDDI; and iodized oils) sources of iodine. The iodine milk content is also affected by seasonal and regional variations (Pennington, 1990), stage of lactation (Swanson, 1972) and use of iodophor postmilking teat dipping (Galton et al, 1984(Galton et al, , 1986Galton, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…feeds and veterinary fortification with inorganic (KI) or organic (ethylenediamine dihydroiodide, EDDI; and iodized oils) sources of iodine. The iodine milk content is also affected by seasonal and regional variations (Pennington, 1990), stage of lactation (Swanson, 1972) and use of iodophor postmilking teat dipping (Galton et al, 1984(Galton et al, , 1986Galton, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a common practice on seasonal farms in Ireland to omit teat preparation entirely prior to cluster application (Kelly et al, 2009;O'Connell et al, 2013). Many authors have demonstrated that among all pre-milking procedures, a wet cleaning treatment followed by manual drying with paper resulted in the lowest milk bacterial counts (Galton et al, 1984;McKinnon et al, 1990;Gibson et al, 2008). The practice of dry wiping teats to remove debris prior to cluster attachment was also associated with lowering the presumptive Bacillus cereus count in bulk tank milk when animals were managed outdoors .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers (Hogan at el. 1979, Galton et al 1984) reported higher coliform count related to the degree of wetness of udder. Patrova and Patrova (1985) in a study showed that udder disinfection (Cl 5ppm) can half the coliform count in milk, whereas Sakya and Srivastava Kantona and Szita (1982).…”
Section: Coliform Count (Cc)mentioning
confidence: 99%